2003 IEEE International Conference on Robotics and Automation (Cat. No.03CH37422)
DOI: 10.1109/robot.2003.1241885
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous localization and mapping with unknown data association using FastSLAM

Abstract: Abstract-The Extended Kalman Filter (EKF) has been the de facto approach to the Simultaneous Localization and Mapping (SLAM) problem for nearly fifteen years. However, the EKF has two serious deficiencies that prevent it from being applied to large, realword environments: quadratic complexity and sensitivity to failures in data association. FastSLAM, an alternative approach based on the Rao-Blackwellized Particle Filter, has been shown to scale logarithmically with the number of landmarks in the map [10]. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
332
0
5

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 466 publications
(410 citation statements)
references
References 13 publications
0
332
0
5
Order By: Relevance
“…For example, the spatial module we describe below would not be appropriate for nor have the accuracy and resolution of state-of-the-art simultaneous localization and mapping (SLAM) algorithms (Montemerlo & Thrun, 2003). A SLAM algorithm, however, while useful to a robot during its own localization and navigational process, is not at all useful when trying to understand why humans systematically think they are closer to landmarks than they really are.…”
Section: Act-r/embodiedmentioning
confidence: 99%
“…For example, the spatial module we describe below would not be appropriate for nor have the accuracy and resolution of state-of-the-art simultaneous localization and mapping (SLAM) algorithms (Montemerlo & Thrun, 2003). A SLAM algorithm, however, while useful to a robot during its own localization and navigational process, is not at all useful when trying to understand why humans systematically think they are closer to landmarks than they really are.…”
Section: Act-r/embodiedmentioning
confidence: 99%
“…Each filter estimates the position of the a single landmark given the current pose estimate. In this sense, our approach is similar to FastSLAM [19]. The difference to FastSLAM is that the partially initialised features x new:j are not used for state estimation immediately.…”
Section: Feature Initialisationmentioning
confidence: 99%
“…Most of the work targeted problems for mobile robot localization [21][22][23]. In Markov localization for mobile robots, the absence of an expected measurement can be used to improve localization.…”
Section: Related Workmentioning
confidence: 99%
“…However, all these works only consider cases where an expected observation is missing. In [23] the authors have shown how negative information can be incorporated into FastSLAM, a system that is alternative to the complex Extended Kalman Filter approach for robot localization. In wireless sensor localization, Monte-Carlo localization algorithms make use of negative information [24].…”
Section: Related Workmentioning
confidence: 99%